1999
DOI: 10.1109/55.772374
|View full text |Cite
|
Sign up to set email alerts
|

A novel 6H-SiC power DMOSFET with implanted p-well spacer

Abstract: In this letter, we utilize a lower thermal budget with an aluminum doped p-well to minimize the effect of "step bunching" and a new structural design with deep spacer implants to prevent the JFET "pinching" action at small p-well spacings (5 m) in planar vertical double implanted MOSFET (DIMOS) devices fabricated on 6H-SiC. A specific ON-resistance of 42 m-cm 2 (further reducible by 35% through simple design modification), which represents a 100% reduction over devices which did not receive the spacer implants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The wide bandgap semiconductor properties of silicon carbide (SiC) make it a promising candidate for the development of future power switching devices [1,2]. This is primarily due to SiC possessing properties such as a strong breakdown field, high physical and chemical stability, high thermal conductivity, and high electron saturation velocity [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The wide bandgap semiconductor properties of silicon carbide (SiC) make it a promising candidate for the development of future power switching devices [1,2]. This is primarily due to SiC possessing properties such as a strong breakdown field, high physical and chemical stability, high thermal conductivity, and high electron saturation velocity [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…JFET region design, including the JFET width and doping concentration, plays a crucial role in optimizing the and switching performance of SiC MOSFETs [ 4 ]. Studies of JFET region design for 1 and SiC MOSFETs [ 5 , 6 ] have demonstrated that optimizing JFET width and enhancing the doping concentration of the JFET region can reduce the JFET region resistance and lead to smaller of SiC power MOSFETs.…”
Section: Introductionmentioning
confidence: 99%
“…On the (0001) Si face, the interface trap density (Dit) near the conduction band edge is high and the Dit strongly affects channel mobility [5]. Thus, the other approach to improving channel mobility is to use a specific surface for the channel region such as the (11 2 0) or (03 3 8) [6].…”
Section: Introductionmentioning
confidence: 99%